2022
DOI: 10.1590/s2175-97902022e19613
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical care and evaluation of adherence to antiretroviral therapy in people living with HIV/AIDS

Abstract: Highly Active Antiretroviral therapy (HAART) depends on optimal adherence to be effective. Pharmacotherapeutic follow-up can be used as a strategy for treatment fidelity. To provide pharmaceutical care for HAART patients, to assess adherence, to identify and resolve drug related problems (DRP). This is a prospective, interventional study aimed at people on HAART. Data was collected using the pharmacotherapeutic follow-up form and CEAT-VIH. There was a predominance of women (59.1%), older than 33 years (75%), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Documentation is a vital aspect of PC which is required for continuity of care, research reimbursement and evidence of action taken 12 . Most pharmacists in the study reported identifying drug therapy problems and followed up with suitable interventions which is similar to a study in Brazil by Schoenherr et al in which PC services were carried out with corresponding interventions 18 . However, only few respondents in this study documented drug therapy problems and their corresponding interventions.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Documentation is a vital aspect of PC which is required for continuity of care, research reimbursement and evidence of action taken 12 . Most pharmacists in the study reported identifying drug therapy problems and followed up with suitable interventions which is similar to a study in Brazil by Schoenherr et al in which PC services were carried out with corresponding interventions 18 . However, only few respondents in this study documented drug therapy problems and their corresponding interventions.…”
Section: Discussionsupporting
confidence: 61%
“…Inter-professional team collaboration is when several health workers from various professional backgrounds provide comprehensive services by working with patients, their families, carers and communities to achieve the highest quality of care 24 .Research shows that when inter-professional team practice collaboratively, patient-centred care is enhanced and there is an improvement in patient and health systems outcomes [25][26] . Pharmacists have the ability to assess patients with virologic failure, evaluate reasons for failure such as non-adherence to ART and provide education on new antiretroviral regimens, thus they are an integral part of the multidisciplinary management of HIV positive patients 18 . Pharmacists have the ability to contribute to every component of HIV care.…”
Section: Discussionmentioning
confidence: 99%